THE AGE-OLD CONFLICT - Corner, Creative (Journal of Pakistan Psychiatric Society, 2023)
The Age-Old Conflict between good and evil is a common theme in mythology, religion, philosophy, and arts. It is often depicted as a battle between two opposing forces, with “good” representing light, order, and justice, and “evil” representing darkness, chaos, and destruction, and ultimately this clash resulting in good triumphing over evil.